The Physics of Kilonovae - Barnes, Jennifer (Frontiers in Physics, 2020)
The science returns of gravitational wave astronomy will be maximized if electromagnetic counterparts to gravitational-wave sources can be identified. Kilonovae are promising counterparts to compact binary mergers, both because their long timescales and approximately isotropic emission make them relatively easy to observe, and because they offer astronomers a unique opportunity to probe astrophysical heavy-element nucleosynthesis and merger-driven mass ejection. In the following, I review progress in theoretical modeling that underpinned advances in our understanding of kilonovae leading up the first detection of a neutron star merger, GW170817. I then review the important lessons from this event and discuss the challenges and opportunities that await us in the future.